Plasmocitoma da coluna lombar - Andrade, DR (2015)
Solitary bone plasmacytoma is a plasma cell disorder characterized by the formation of a single tumor in the bone. Most commonly, the tumor develops in the spine, and is progressively less frequent in the pelvis, ribs, upper extremities, skull, femur and sternum. Symptoms are mainly local. In most cases, multiple myeloma ensues, conferring it a poor prognosis. The authors describe the case of a 53-year-old male patient who presented with persistent low back pain without apparent cause until a radiography of the lumbar spine was performed. It revealed a lytic lesion, which was proven to be a plasmacytoma after a computed tomography guided biopsy.